Sintering of copper-alumina composites through blending and mechanical alloying powder metallurgy routes - Upadhyaya A.; Upadhyaya G.S. (My University, 2025)
Dispersion-strengthened copper has the ability to retain most of its properties at elevated temperatures. Among various processes, the powder metallurgy preparation route is ideal because of its efficient dispersion of fine particles. In the present investigation copper composites containing 0-3 wt%. Al2O3 were sintered in hydrogen at temperatures of 800°C and 900°C. The powders were prepared through the blending and mechanical alloying routes. The green compaction pressures were 500 and 560 MPa, respectively. With an increase in compaction pressure both sintered density and hardness increased. It was found that densification kinetics were faster for mechanically alloyed powder compacts than the blended ones. An increase in Al2O3 content in general increased hardness, with an associated loss in electrical conductivity. © 1995.